Cryopreservation of equine and canine monocyte derived dendritic cells - Deeb, Tarek; Schwebel, Felix; Winkler, Christina; Dettmer-Richardt, Claudia; Rebeski, Dierk; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):232